The Study Of Motivational Drives Among Degree College Students With Special Reference To Mcclelland's Theory Of Motivation- A Case Example - Manglani, Kiran (SFIMAR Research Review, 2017)
Motivation is the drive or need which influences people to strive or put effort. There are various motivational theories which are categorized into process theories and content theories. The wellknown theory of all is the McClelland's theory of motivation wherein he classified the people influenced by three types of drives viz; Achievement, Power and Affiliation. Different types of people experience different drives in different phases of life. The study is based on Likert scale analysis of R. Steers and D. Braun stein test of finding out different drives of motivation in the selected groups as stated by McClelland and thereby highlighting different factors and traits of personality in relation to motivation.